A study on the factors that influence women involvement in entrepreneurships / Amiruddin Bahrom Azhar - Bahrom Azhar, Amiruddin (2012)
This exploratory research was carried out on women entrepreneurs in Kelantan with the aim to identify the factors that influence them to involve in entrepreneurship. This study was based on simple random sampling method based on MARA customers and the data was collected after they are answers the entire question required. This study also implemented on 50 respondents. Questionnaires were distributed and the data gathered was analyzed to derive possible findings of the study. For this study, a Multiple Linear Regression had been use to measure the relationship between the dependent variable (Women Entrepreneurs) and the factors of influence the involvement (Family, Culture, and Academic Level).While conducting this study, it also has several implications such as information constraint, lack of cooperation from respondents and also misinterpretation towards questionnaire. This research also included some recommendations that related to the study which is maybe can help women entrepreneurs to survivelonger in the business